Е.Э.БЕРТЕЛЬС ИЖОДИДА АБУ НАСР ФАРОБИЙ ФАЛСАФАСИ ТАЛҚИНИ - Туробов, Б.Н. (SCIENCE and SOCIETY, 2020)
The article discusses the scientific research of the orientalist scientist E.Bertels about encyclopedic scholar Farobi's scientific activity, philosophy and contribution to the development of science in Central Asia and in the world. It was also mentioned about Central Asian cities becoming the important scientific centers in the 10th century; the encyclopedic scientists who have made huge contribution to the world science with their philosophical views.
Keywords: Abu Nasr Farobi; Aristotle; Plato; Porphyry; "The City of Noble People"; "Metaphysics"; "Sources of phylosophy"; "Introduction to science of logics"